2021
DOI: 10.3389/fcimb.2021.804253
|View full text |Cite
|
Sign up to set email alerts
|

Anticolonization of Carbapenem-Resistant Klebsiella pneumoniae by Lactobacillus plantarum LP1812 Through Accumulated Acetic Acid in Mice Intestinal

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is highly prevalent and poses a significant threat to public health. In critically ill patients, gut colonization is considered to be the reservoir of recurrent CRKP infection. Therefore, eliminating CRKP carriage in the intestine is critical for preventing subsequent CRKP infection. In the present study, Lactobacillus plantarum LP1812, a probiotic that can inhibit CRKP in vitro, was used as a candidate probiotic to investigate its efficacy for CRKP anticoloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Recent studies have reported that the anticolonization of K. pneumoniae by Lactobacillus spp. was attributed to increased acetic acid and regulation in microbiota in mice intestinal [ 29 , 34 ]. To investigate the mechanism underlying the inhibition of CR-hvKP colonization by Lactobacillus spp., we repeated the K. pneumoniae colonization experiment and replaced Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that the anticolonization of K. pneumoniae by Lactobacillus spp. was attributed to increased acetic acid and regulation in microbiota in mice intestinal [ 29 , 34 ]. To investigate the mechanism underlying the inhibition of CR-hvKP colonization by Lactobacillus spp., we repeated the K. pneumoniae colonization experiment and replaced Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…The co-culture assay was performed as previously described [ 29 ]. K. pneumoniae and Lactobacillus spp.…”
Section: Methodsmentioning
confidence: 99%
“…4). Although Lp producing acetic acid might inhibit Ec 29, 30, 31 , the media developed for Ec growth (M1-3_Ec) remained specificity in the presence of Lp . The results suggested that the ML-assisted medium optimization and specialization were practical, and the resultant media were robust regardless of mono- or co-culture.…”
Section: Resultsmentioning
confidence: 99%
“…Using in vitro approaches or mice models of multiresistant K. pneumoniae intestinal colonization, it was demonstrated that some Lactobacillus spp. strains diminished the pathogen colonization and biofilm formation [ 8 , 9 , 10 , 11 , 12 ]. The ability of lactobacilli to inhibit the colonization of K. pneumoniae was associated with organic acid production [ 10 , 11 ] and the secretion of proteins with antimicrobial activity [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…strains diminished the pathogen colonization and biofilm formation [ 8 , 9 , 10 , 11 , 12 ]. The ability of lactobacilli to inhibit the colonization of K. pneumoniae was associated with organic acid production [ 10 , 11 ] and the secretion of proteins with antimicrobial activity [ 13 , 14 ]. In addition, few studies reported that the oral administration of probiotic microorganisms to mice significantly reduced the lung inflammatory damage induced by K. pneumoniae nasal challenge [ 15 , 16 ], demonstrating that immunomodulatory bacteria are an interesting alternative to enhance resistance to this pathogen.…”
Section: Introductionmentioning
confidence: 99%